2022
DOI: 10.1155/2022/4573629
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] A Public Health‐Oriented New Energy Industry Competitiveness Evaluation

Abstract: This paper develops a regional new energy industry (NEI) competitiveness evaluation index system based on the theoretical framework of the “diamond model” and the unique characteristics of the new energy industry and made an empirical analysis of Jilin province with analytic hierarchy process (AHP) and fuzzy comprehensive evaluation method. The analysis results show that the new energy industry in Jilin Province has a good foundation, and the government’s role, talent support, technological innovation, and mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…For example, Busu (2019) used panel data model to quantitatively evaluate the environmental policies of EU member states and analyze the impact of their environmental policies on new energy industry agglomeration. Dou et al (2022) constructed the evaluation index system of the competitiveness of new energy industry clusters in Jilin Province and conducted empirical analysis through GEM and AHP models. Research on spatial agglomeration of new energy industry such as Xu et al (2022) used coupling model to analyze the coupling relationship between new energy industry agglomeration and regional knowledge carrying capacity.…”
Section: Spatial Evolution Of New Energy Industrymentioning
confidence: 99%
“…For example, Busu (2019) used panel data model to quantitatively evaluate the environmental policies of EU member states and analyze the impact of their environmental policies on new energy industry agglomeration. Dou et al (2022) constructed the evaluation index system of the competitiveness of new energy industry clusters in Jilin Province and conducted empirical analysis through GEM and AHP models. Research on spatial agglomeration of new energy industry such as Xu et al (2022) used coupling model to analyze the coupling relationship between new energy industry agglomeration and regional knowledge carrying capacity.…”
Section: Spatial Evolution Of New Energy Industrymentioning
confidence: 99%
“…)» [22]. В этой связи позволительно поставить в один ряд два тренда современной цивилизации в целом: развитие «зеленой энергетики» (цель которой -«оздоровление» биосферы в ситуации современного экологического кризиса) и развитие «индустрии здоровья» (цель которой в сбережении, укреплении здоровья) [32,33].…”
Section: здоровье как факт норма и ценностьunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%